Panaceas and pitfalls in electrodriven chromatographic techniques - Buica, Astrid Sorina (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2007.